2022
DOI: 10.1002/er.8563
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic activity and diode performance of ZnO‐GO nanocomposites via doping with aluminum

Abstract: Herein, a twofold enhancement tactics were served to boost the photocatalytic activity as well as the diode performance of ZnO. The combination of aluminum (Al) and graphene oxide (GO) with ZnO fostered photocatalytic efficiency on Cong red (CR) and magnified the rectification of The Ag/n-Zn 1Àx Al x O-GO/ p-Si/Al heterostructure diode. Zn 1Àx Al x O-GO nanocomposites (x = 0.0, 0.03, 0.05, and 0.07 mol, GO = 2 wt.%) were successfully synthesized by solvothermal approach as confirmed by X-ray diffraction (XRD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…As can be noted, the surface becomes much smoother in a magnetized state. The roughness has been determined as described previously, , and it has been found that the roughness values of the pristine, magnetized, and demagnetized Cu 1.8 Se 0.6 S 0.4 electrodes are 14.49, 11.71, and 14.18 nm, respectively. The reduction in the roughness of the magnetized sample may be due to the change of the form from a nanosphere to a nanoflower.…”
Section: Resultsmentioning
confidence: 99%
“…As can be noted, the surface becomes much smoother in a magnetized state. The roughness has been determined as described previously, , and it has been found that the roughness values of the pristine, magnetized, and demagnetized Cu 1.8 Se 0.6 S 0.4 electrodes are 14.49, 11.71, and 14.18 nm, respectively. The reduction in the roughness of the magnetized sample may be due to the change of the form from a nanosphere to a nanoflower.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of rGO on the roughness of the P 3HT can be examined by the surface 3D view of the FESEM, as shown in Figure 5C,D. The root means square roughness( R q ) and the average roughness ( R a )was estimated from the line profile manifested in Figure 5E,F, by employing the below formulas 51,52 : Rqgoodbreak=i=1NZiZa2N,$$ {R}_q=\sqrt{\frac{\sum \limits_{i=1}^N{\left({Z}_i-{Z}_a\right)}^2}{N},} $$ Ragoodbreak=i=1N||Zigoodbreak−ZcpN,$$ {R}_a=\sqrt{\frac{\sum \limits_{i=1}^N\left|{Z}_i-{Z}_{\mathrm{cp}}\right|}{N},} $$ where Z i is the current Z value, Z a denotes the average Z value of the investigated area, N expresses the number of points, and Z cp is the Z value of the center plane 53 . The R q and R a for pristine were found to be 13.3 and 12.65 nm, whereas rGO/P3HT (10 wt5%) have higher roughness of about 21.25 and 19.56 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5C,D. The root means square roughness(R q ) and the average roughness (R a )was estimated from the line profile manifested in Figure 5E,F, by employing the below formulas 51,52 :…”
Section: Morphological and Compositional Investigationmentioning
confidence: 99%
“…Maxilon blue dye was used as a model organic pollutant and its structure is represented in Figure 1. The photodegradation experiments were conducted to evaluate the photocatalytic performance of AgBiSe 2 /PVDF/PEO membranes, a 200 mL beaker containing a 50 mg/L Maxilon blue dye solution was maintained in the dark for 30 min while being stirred by a magnetic stirrer to establish adsorption–desorption equilibrium 40 . After that, solar light was directed straight down onto the beaker.…”
Section: Methodsmentioning
confidence: 99%
“…The photodegradation experiments were conducted to evaluate the photocatalytic performance of AgBiSe 2 /PVDF/PEO membranes, a 200 mL beaker containing a 50 mg/L Maxilon blue dye solution was maintained in the dark for 30 min while being stirred by a magnetic stirrer to establish adsorption-desorption equilibrium. 40 After that, solar light was directed straight down onto the beaker. A 5-ml aliquot of the reaction solution was obtained to determine the efficacy of the decolorization.…”
Section: Photocatalytic Experimentsmentioning
confidence: 99%